Antimicrobial activity and phytochemical analysis of crude extracts and essential oils from medicinal plants - Silva, N. C. C. [UNESP]; Barbosa, L. [UNESP]; Seito, L. N. [UNESP]; Fernandes Junior, A. [UNESP] (Taylor & Francis Ltd, 2012)
We aimed to establish a phytochemical analysis of the crude extracts and performed GC-MS of the essential oils (EOs) of Eugenia uniflora L. (Myrtaceae) and Asteraceae species Baccharis dracunculifolia DC, Matricaria chamomilla L. and Vernonia polyanthes Less, as well as determining their antimicrobial activity. Establishment of the minimal inhibitory concentrations of the crude extracts and EOs against 16 Staphylococcus aureus and 16 Escherichia coli strains from human specimens was carried out using the dilution method in Mueller-Hinton agar. Some phenolic compounds with antimicrobial properties were established, and all EOs had a higher antimicrobial activity than the extracts. Matricaria chamomilla extract and E. uniflora EO were efficient against S. aureus strains, while E. uniflora and V. polyanthes extracts and V. polyanthes EO showed the best antimicrobial activity against E. coli strains. Staphylococcus aureus strains were more susceptible to the tested plant products than E. coli, but all natural products promoted antimicrobial growth inhibition.
Keywords: plant crude extracts; essential oils; medicinal plants; minimal inhibitory concentration; antibacterial activity; phytochemical analysis